POTENSI UPACARA ADAT SEBAGAI PENGGERAK EKONOMI YANG BERKELANJUTAN DI TANAH TORAJA - Priyendiswara Agustina Bela (PROSIDING SERINA, 2021)
The traditional ceremony in Tanah Toraja is one of the traditional activities that are widely known in the world. This traditional ceremony is more often conducted by the Torajanese today than a few decades ago. The problem that becomes the focus of this observation is the animals used in the traditional ceremony, because they are traded on a very large area and specifically sell animals that will be used for traditional ceremonies. This animal trading activity became very interesting to discuss because it turned out that the animals were imported from various places. So that this activity can be considered as an economic driver, it is necessary to find out its sustainability, how much is the demand for these animals and what is their economic value? This research was conducted by conducting interviews, literature review and field surveys. The results of this study are to determine the types of animals used in traditional ceremonies and their economic value and the impact of traditional ceremonies in Tanah Toraja on improving the economy of the Tanah Toraja people and people in Indonesia related to this activity and also the impact of traditional ceremonies on the tourism in Tanah Toraja. The conclusion is that traditional ceremonies in Tanah Toraja can be an economic driver for the Torajanese and the people of the area around Tanah Toraja and even in Indonesia at large. Likewise, it is recommended to use information technology to support the implementation of the traditional ceremony.Upacara Adat di Tanah Toraja merupakan salah satu kegiatan adat yang sudah dikenal cukup luas di dunia ini. Upacara adat ini semakin sering dilakukan oleh suku Toraja saat ini dibandingkan beberapa puluh tahun yang lampau. Masalah yang menjadi fokus pengamatan adalah hewan-hewan yang digunakan dalam upacara adat tersebut, karena diperjual belikan dilahan yang sangat luas dan khusus menjual hewan yang akan digunakan untuk upacara adat. Kegiatan jual beli hewan ini menjadi sangat menarik untuk dibahas karena ternyata hewan-hewan tersebut didatangkan dari berbagai tempat. Sehingga kegiatan ini dapat dianggap sebagai penggerak ekonomi yang perlu dicari tahu keberlanjutannya, berapa besar permintaan terhadap hewan tersebut dan berapa nilai ekonominya? Penelitian ini dilakukan dengan melakukan wawancara, tinjauan Pustaka dan survei lapangan. Hasil dari penelitian ini yaitu mengetahui jenis-jenis hewan yang digunakan pada upacara adat dan nilai ekonominya dan dampak dari upacara adat di Tanah Toraja terhadap peningkatan ekonomi masyarakat Tanah Toraja dan masyarakat di Indonesia yang terkait dengan kegiatan ini, selain itu juga dampak dari upacara adat terhadap pariwisata di Tanah Toraja. Kesimpulannya adalah upacara adat di Tanah Toraja dapat menjadi penggerak ekonomi bagi masyarakat Toraja dan wilayah disekitar Tanah Toraja dan bahkan di Indonesia secara luas. Demikian juga direkomendasikan pemanfaatan informasi teknologi untuk mendukung penyelenggaraan upacara adat tersebut.